KARAKTERISTIK ORGANOLEPTIK DAN KIMIAWI SNACK POCKET STICK KACANG MERAH (Phaseolus vulgaris L) DENGAN PENAMBAHAN IKAN TERI (Stolephorus sp) SEBAGAI KUDAPAN SEHAT ANAK SEKOLAH - Yulia Silvianti Cidi; Yuges Saputri (FoodTech: Jurnal Teknologi Pangan, 2019)
Food consumed by school children commonly contains low levels of macro and micro nutrients. Eating habits which is consuming low-nutrient foods in school children may affect the nutritional status and will ultimately lead to their ability in learning activities at school. This study aims to determine the level of organoleptic acceptance and chemical properties of red bean (Phaseolus vulgaris l) stick pocket  with the addition of anchovies (Stolephorus sp) intended for school children. This research is experimental, using a Completely Randomized Design (CRD) and Visual Analog Scale (VAS) instrument as well as a Likert scale. Based on the results of the analysis, there were no significant differences in all parameters (color, taste, aroma, texture, taste, and overall) both the hedonic value and the hedonic quality. The best pocket stick nutrient content is in the formulation with the addition of 80 grams of anchovies and 70 grams of red beans that has a water content of 4.10%, ash content of 3.32%, fat content of 3.84%, protein content of 14.6%, carbohydrate content of 54.08%, fiber content crude 6.00 mg, and calcium levels 147.08 mg. Thus snack pocket sticks can be used as additional food for school children